Nanobacteria in the pathogenesis of urolithiasis: Myth or reality? - Abrol, Nitin (Indian J Urol, 2015)
Stone formation in the urinary tract is a common phenomenon with associated morbidity. The exact physicochemical factors responsible for stone formation are not clearly known. Over the past decade considerable interest has been generated in defining the role of nanobacteria in urinary stone formation. A review of the available literature has been carried out to give insights into their nature and outline their role in stone formation. The two aspects of nanobacteria that need to be considered include its biological nature and the other merely as mineralo-protein complexes. Though the current literature favors the concept of mineralo-protein particles, further research is needed to clearly define their nature. Whether living or nonliving, these apatite forming nanoparticles appear to play role in kidney stone formation.